(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2018)
Bioinformatics is an interdisciplinary field of biomedical engineering and biotechnology that incorporates computational, mathematical, statistical analysis and information technology to provide a better solution to biological and biomedical engineering problems. Bioinformatics aims at the advancement of biomedical engineering by furnishing an open platform for biomedical engineers, researchers, educators, and scientists.Biomedical engineering and bioinformatics is experiencing remarkable expansion and recognition at present. Applied bioinformatics is thus right now is a hot, alluring and captivating field that incorporates life sciences, biomedical sciences, computationl biology and software engineering for better future of mankind.